The global economics of sport - Gratton, Chris, 1948- (Routledge, 2012)
"Sport has become a global business. There is no corner of the Earth that isn't reached by coverage of global sporting mega-events such as the Olympics or the World Cup, events managed by international governing bodies such as the IOC and FIFA that operate like major international businesses. Companies such as Nike now design, produce, distribute and market their products across every continent, while an increasingly important part of every country's sport market is now international in terms of its influences and opportunities. This book is the first to examine the economics of contemporary sport using the global market as the primary unit of analysis. Starting with a survey of the changing nature of the sports market over the last hundred years, the book explores the difficulties of measuring the true scale and impact of the global sports economy, employing a wealth of empirical data to define and analyze the sports market and all its sub-sectors. Drawing on case studies from the UK, North America, Europe, the Far East and beyond, the book concludes with a look forward over the next twenty years, offering a powerful forecast for the evolution of the global sports market. This book is essential reading for any student or professional with an interest in the economics of sport"--Vydavatelská anotace
Keywords: sport; ekonomika sportu; globalizace; sports; sports economics; globalization; studie; studies